Immunogenicity of genotype-matched Newcastle disease virus vaccine following two doses of drinking water vaccination in specific-pathogen-free chickens - Chan, Huan Sheng
Newcastle Disease (ND) has severely impacted the poultry industry worldwide due to high mortality in birds. Despite the use of various Newcastle disease virus (NOV) vaccines, outbreaks caused by genotype VII NDV have been continuously reported among vaccinated farms. The purpose of this study was to examine the effect of dose of vaccine virus on the immunogenicity of the genotype-matched NOV vaccine, mIBS025 and its optimal dose following double drinking water (DW) vaccination in specific pathogen-free (SPF) chickens. A total of 75 day-old SPF chickens were divided into five groups with 15 birds each. Group 1 was administered with phosphate-buffered saline as unvaccinated control. Group 2, 3, 4 and 5 were vaccinated with 104•5, 105, 105•5 and 106 embryo infectious dose 50 (EID50) of mIBS025 vaccines at day-old and 14 days-old via DW, respectively. Blood was collected from the chickens weekly for five weeks after primary vaccination. NDV antibody titers at each point were evaluated using haemagglutination inhibition (HI) test. Results showed that at 21 days-old or one week after booster vaccination, chickens vaccinated at 105, 105•5 and 106 EID50 had HI titers of 5.42log2, 6.27log2, and 5.22log2, respectively, which significantly (p>0.05) higher than 104•5 EID50 (3.7llog2) but no significant difference among them (p>0.05). Vaccination dose of 105•5 EID50 induced significantly (p>0.05) higher HI titers (6.38log2) than 104•5 EID50 (5.04log2) at 28 days-old or 14 days after booster vaccination. Current study demonstrated that 105•5 EID50 is the optimal dose of mIBS025 vaccine in inducing HI antibody titer in SPF chickens.